"Sustainability" Education by Sustainable School Design. (13th May 2015) - Tascı, Burcu Gulay
Abstract: In recent years, sustainability concept has become the common interest of numerous disciplines. The reason for this popularity is, to perform the sustainable development of societies. Easiness of forming a relationship with the word "sustainability" is because of its social, economic and environmental aspects. The term provides different perspectives to different areas. Today, in educational sciences, "environmental sustainability" is one of the main subjects that lesson programs include several studies about. In education system in Turkey, to teach "sustainability" concept, teachers uses traditional education methods mostly. To tell "what sustainability is" only by words is not enough for using the knowledge in the practice. Besides this, students learn much more by seeing real examples rather than hearing about it. In this context, this study aims to nominate "school buildings" as valuable learning environments for students. In other words, school buildings can be seen as 3D text books written by architects. Architecture discipline deals with environmental sustainability and defines various sustainability criteria. Environmental sustainability is related with built environment design and designing with the natural environment. In this study, sustainable school buildings had been analysed related with their design criteria and as a result an evaluation made about using architecture and its products as a concrete material for sustainability education.